Assessment of variability for yield, component traits and reaction to foliar fungal diseases in back cross population of groundnut (Arachis hypogaea L.): ASSESSMENT OF VARIABILITY FOR YIELD AND REACTION TO FUNGAL DISEASES IN GROUNDNUT - P RAMAKRISHNAN; N MANIVANNAN; L MAHALINGAM (Journal of Oilseeds Research, 2016)
Three BC1F1 populations viz., TMV (Gn) 13 × GPBD 4, CO 7 × GPBD 4 and TMV 2 × GPBD 4 along with their parental lines of groundnut were evaluated for variability, heritability and genetic advance. High magnitude of PCV and GCV coupled with broad sense heritability and genetic advance as per cent of mean for these characters studied such as number of pods per plant, shell weight per plant, rust disease score, late leaf spot (LLS) disease score, pod yield per plant and kernel yield per plant in all the populations. So, it could be concluded that these characters were under the control of additive type of gene action and hence selection may be effective for these traits in these populations.